Detection of serum antibodies to parainfluenza type 3 virus, respiratory syncytial virus, bovine viral diarrhea virus, and herpes virus type 1 in sheep in the region of Botucatu, São Paulo - Brazil - Gonçalves, Roberto Calderon [UNESP]; Silva, Andreza Amaral da [UNESP]; Ferreira, Danilo Otávio Laurenti [UNESP]; Marcondes, Júlio Simões [UNESP]; Pituco, Edwiges Maristela; Dias, Adriano [UNESP] (My University, 2011)
Occurrence of various livestock diseases particularly foot and mouth disease, infectious bursal disease, contagiuos bovine pleuro pneumonia, babesiosis and trypanosomosis were established among the Fulani community of Barkin Ladi Local Government Area, Plateau State. For this study, different techniques of participatory rural appraisal such as open-ended interview, probing, triangulation, transect and proportional piling with key informant/translator were applied in randomly selected 30% of the Fulani community. Analysis of data indicated that haemorrhagic septicaemia was the most important while babesiosis and contagious bovine pleuro pneumonia were the most prevalent diseases in the community. Other significant livestock health problems recorded during appraisal exercise were newcastle disease, fascioliasis, brucellosis, tick and tsetse fly infestation. There was no evidence of rinderpest outbreak in the area of investigation during the last 5 years. Participatory rural appraisal proved to be a useful tool to collect reliable data that can be utilized to empower and integrate the rural livestock-owning commuinties in the control/eradication of animal diseases.
Keywords: Sheep; Viral respiratory infections; Serum; Antibody titration; Ovinos; Infecções respiratórias virais; Soro; Titulação de anticorpos